2009
DOI: 10.1021/es8021655
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Source CO2 Mitigation through Smart Growth Development and Vehicle Fleet Hybridization

Abstract: This paper presents the results of a study on the effectiveness of smart growth development patterns and vehicle fleet hybridization in reducing mobile source emissions of carbon dioxide (CO 2 ) across 11 major metropolitan regions of the Midwestern U.S. over a 50-year period. Through the integration of a vehicle travel activity modeling framework developed by researchers at the Oak Ridge National Laboratory with small area population projections, we model mobile source emissions of CO 2 associated with altern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…All groups are analyzed at the U.S. state spatial scale. The national-average approach attempts to reflect the type of analysis typically employed prior to the availability of the Vulcan data product (Southworth et al, 2008;Stone et al, 2009).…”
Section: Comparison Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All groups are analyzed at the U.S. state spatial scale. The national-average approach attempts to reflect the type of analysis typically employed prior to the availability of the Vulcan data product (Southworth et al, 2008;Stone et al, 2009).…”
Section: Comparison Methodsmentioning
confidence: 99%
“…Studies to date, have either focused on only one of these three components, have been completed only at the national scale, or have not explicitly represented CO 2 emissions (Puentes, 2008;Southworth et al, 2008;Stone et al, 2009). Southworth et al (2008) analyzed VMT and CO 2 emissions for the 100 largest metropolitan areas in the U.S. but only disaggregated vehicles into trucks and passenger cars and used a single national estimate of vehicle fuel efficiency for each of the two vehicle types.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, steps to reduce urban air pollutants from motor vehicles may prove beneficial for physical activity levels 40À42 and transportation-CO 2 emissions. 43,44 Our use of regulatory data to estimate long-term populationweighted ambient pollution concentrations at the urban scale is both a strength and a limitation of this study. It is a strength because the data represent widely accepted "gold standard" measurements of air pollution and because our results are based on empirical evidence rather than models or theory.…”
Section: Articlementioning
confidence: 99%
“…Previous work has employed the ASIF (emissions are the product of activity [A], modal share [S], modal energy intensity [I], and fuel mix [F]) and IPAT (environmental impact [I] is the product of population [P], affluence [A], and technology [T]) frameworks to model travel behaviour (GrimesCasey et al, 2009;Schipper et al, 2000;Zegras, 2007) concluded that activity (e.g., VKT per capita) is an important factor in transportation emissions. Recent modelling of the US Midwest suggests that compact growth could achieve long-term emission reductions equivalent to the hybridization of the light duty vehicle fleet (Stone et al, 2009). …”
Section: Introductionmentioning
confidence: 99%